Virtual Reality (VR) for Mental Skills Training in Elite Athletes: A Quasi-Experimental Study - Gonzalez-Fernandes, Francisco Tomas; Fahimi, Mahdi; Brini, Seifeddine (AI and Tech in Behavioral and Social Sciences, 2025)
This Quasi-Experimental Study examined the efficacy of virtual reality (VR)-enhanced mental skills training compared to traditional methods in improving psychological resilience, physiological regulation, and sport-specific performance among elite athletes. Eighty elite athletes (40 male, 40 female) from football, basketball, swimming, and track and field were randomly assigned to either a VR training group (n=40) or a traditional mental skills training group (n=40). The VR group completed six weeks of immersive, biofeedback-assisted sessions using the Meta Quest Pro headset with sport-specific scenarios, while the control group received conventional mental training. Psychological (SMTQ, CSAI-2R), physiological (HRV, EDA), and performance metrics were assessed at baseline, post-intervention, and three-month follow-up. The VR group demonstrated significantly greater improvements in mental toughness (28.6% vs. 12.4%, p < 0.001), faster autonomic recovery (40% reduction in stress recovery time, p = 0.003), and enhanced decision-making under pressure (23% faster correct responses, p < 0.001) compared to controls. Team sport athletes showed larger benefits than individual sport athletes (p = 0.02), and effects were maintained at follow-up with minimal decay (<5%). VR-based mental training outperforms traditional methods, particularly when integrated with biofeedback and sport-specific simulations. These findings support VR as a transformative tool for elite athlete preparation, offering scalable, data-driven psychological training with lasting effects.